Pancreatic Alpha-Cells Contribute Together With Beta-Cells to CXCL10 Expression in Type 1 Diabetes - Nigi, Laura; Brusco, Noemi; Grieco, Giuseppina E.; Licata, Giada; Krogvold, Lars; Marselli, Lorella; Gysemans, Conny; Overbergh, Lut; Marchetti, Piero; Mathieu, Chantal; Dahl Jørgensen, Knut; Sebastiani, Guido; et al. (Frontiers in Endocrinology, 2020)
C-X-C Motif Chemokine Ligand 10 (CXCL10) is a pro-inflammatory chemokine specifically recognized by the ligand receptor CXCR3 which is mostly expressed in T-lymphocytes. Although CXCL10 expression and secretion have been widely associated to pancreatic islets both in non-obese diabetic (NOD) mice and in human type 1 diabetic (T1D) donors, the specific expression pattern among pancreatic endocrine cell subtypes has not been clarified yet. Therefore, the purpose of this study was to shed light on the pancreatic islet expression of CXCL10 in NOD, in C57Bl/6J and in NOD-SCID mice as well as in human T1D pancreata from new-onset T1D patients (DiViD study) compared to non-diabetic multiorgan donors from the INNODIA European Network for Pancreatic Organ Donors with Diabetes (EUnPOD). CXCL10 was expressed in pancreatic islets of normoglycaemic and new-onset diabetic NOD mice but not in C57Bl/6J and NOD-SCID mice. CXCL10 expression was increased in pancreatic islets of new-onset diabetic NOD mice compared to normoglycaemic NOD mice. In NOD mice, CXCL10 colocalized both with insulin and glucagon. Interestingly, CXCL10-glucagon colocalization rate was significantly increased in diabetic vs normoglycaemic NOD mouse islets, indicating an increased expression of CXCL10 also in alpha-cells. CXCL10 was expressed in pancreatic islets of T1D patients but not in non-diabetic donors. The analysis of the expression pattern of CXCL10 in human T1D pancreata from DiViD study, revealed an increased colocalization rate with glucagon compared to insulin. Of note, CXCL10 was also expressed in alpha-cells residing in insulin-deficient islets (IDI), suggesting that CXCL10 expression in alpha cells is not driven by residual beta-cells and therefore may represent an independent phenomenon. In conclusion, we show that in T1D CXCL10 is expressed by alpha-cells both in NOD mice and in T1D patients, thus pointing to an additional novel role for alpha-cells in T1D pathogenesis and progression.